Cover Image. (8th November 2019) - Lizarraga‐Valderrama, Lorena R.; Taylor, Caroline S.; Claeyssens, Frederik; Haycock, John W.; Knowles, Jonathan C.; Roy, Ipsita
Abstract : The cover image is based on the Original Article Unidirectional neuronal cell growth and differentiation on aligned polyhydroxyalkanoate blend microfibres with varying diameters by Lorena R. Lizarraga‐Valderrama,   Caroline S. Taylor, Frederik Claeyssens, et al., https://doi.org/10.1002/term.2911 .